Meningkatkan Hasil Belajar IPS Siswa SD dengan Model Pembelajaran Group Investigation (GI) - Boby Audy Lompoliu (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to describe how the application of the Group Investigation Learning Model can improve social studies learning outcomes, especially in the natural and artificial appearance material of Class V SD GMIM 1 Kanonang. This study used a classroom action research design using a spiral model consisting of 4 stages, namely: planning, action, observation and reflection. Data Sources This research was conducted based on problems in social studies learning at SD GMIM 1 Kanonang, the subject of the action was 1 teacher of Class V, the subject of the recipient of the action was 20 Class V students. The type of data in this study were qualitative and quantitative in the form of student work results, namely evaluation. Data collection techniques, namely through observation and tests. The data analysis technique used the learning outcome mastery formula. From the learning result data obtained, analyzed by calculating the completeness of student learning outcomes, obtained different results from each cycle where in the first cycle the learning outcomes only reached 49.25% while in the second cycle it reached 84.75%. Based on the results of the study, it can be concluded that using the Group Investigation Model can improve social studies learning outcomes on the natural and artificial appearance material of class V SD GMIM 1 Kanonang. It is hoped that in the learning process students will be more active and play an active role in the learning process.